Bacterial Spore Antigens: a Review - NORRIS, J. R (Journal of general microbiology, 1962)
Department of Bacteriology, University of Glasgow ABSTRACT SUMMARY: Agglutinogens and precipitinogens have been detected in the spores of many species of aerobic and anaerobic spore-formers and these antigens are distinct from those of the vegetative growth phases of the corresponding organisms. Spore antigens are heat resistant and antibody response is elicited by the injection of autoclaved spores into rabbits. Injection of living spores leads to the development of antibodies reacting with vegetative cell antigens in addition to spore antibodies. Agglutinogens tend to show subspecies distribution in some aerobic species but spore precipitinogens appear to be mainly species specific in aerobes. Less information is available about anaerobes where a similar pattern of specificity is suggested. Data about the antigenic structure of the spore and the antigenic changes accompanying sporulation and germination are scant; it is in these aspects of the subject that the most significant progress is to be anticipated.